2008
DOI: 10.1080/15438620802103999
|View full text |Cite
|
Sign up to set email alerts
|

Lower Limb Coordination and Stiffness During Landing from Volleyball Block Jumps

Abstract: Abstract.The aim of the study was to investigate lower limb coordination and stiffness in five male and five female university volleyball players performing block jump landings. Coordination was assessed using angle -angle plots of the hip -knee, knee -ankle and hip -ankle joint couplings and discrete relative phase (DRP) of right -left joint couplings (i.e. left knee coupled with right knee). Leg stiffness was calculated as the ratio of the change in vertical ground reaction force (GRF) to the change in verti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
60
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 19 publications
(25 reference statements)
9
60
1
2
Order By: Relevance
“…In a previous volleyball block jump task, leg stiffness during landing from a volleyball block jump was reported as 15.02 kN/m (Hughes & Watkins, 2008), which is similar to the values observed in the current study (13.62 kN/m). These similarities in leg stiffness values may be due to the similar task involved.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In a previous volleyball block jump task, leg stiffness during landing from a volleyball block jump was reported as 15.02 kN/m (Hughes & Watkins, 2008), which is similar to the values observed in the current study (13.62 kN/m). These similarities in leg stiffness values may be due to the similar task involved.…”
Section: Discussionsupporting
confidence: 90%
“…Dynamic stability of the leg is determined by the coordination between the ankle, knee, and hip joints during landing and is reflected in the stiffness of the leg (Hughes & Watkins, 2008). In a previous volleyball block jump task, leg stiffness during landing from a volleyball block jump was reported as 15.02 kN/m (Hughes & Watkins, 2008), which is similar to the values observed in the current study (13.62 kN/m).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, research concerning the alteration of stiffness that also includes both sexes during landing is limited. Granata, Padua, and Wilson (2002) and Hughes and Watkins (2008) found that females have less stiffness than males during hopping and volleyball block jumps, which may be associated with the greater risk of ACL injury in females.…”
mentioning
confidence: 99%